Appropriateness of hydrokinesitherapy in the orthopedic-traumatological patient: a cross sectional survey - Troiano, Gianmarco; Della Polla, Generoso; Cavuoto, Fulvio; Taglione, Elisa; Nante, Nicola (Revista Cubana de Ortopedia y Traumatología, 2022)
Introduction: Hydrokinesitherapy is a rehabilitation method used for the treatment of different types of orthopedic, neurological, respiratory problems, etc. However, the existing literature presents not so much evidence regarding the greater efficacy of water treatment compared to dry treatment in patients with post-traumatic outcomes. Objective: Through the administration of a questionnaire, we tried to investigate the rehabilitation experience of hydrokinetic therapists (trained with the so-called Sequential and Preparatory Approach) in order to understand hydrokinesitherapy areas and methods of proper application based on experts’ opinion. Methods: A cross-sectional study was carried out in 2020 by administering a questionnaire to physiotherapists trained in hydrokinesitherapy according to the Sequential and Preparatory Approach method, with the aim to investigate their opinion on the use of hydrokinesitherapy in patients with various orthopedic-traumatological problems. Microsoft FORMS® platform was used for the administration of the questionnaire. Results: Sixty-two users participated in the study. From their answers emerged that the use of hydrokinesitherapy is not recommended for the treatment of post-traumatic hypersensitization of peri-lesional tissues (hypersensitive scars; general hypersensitization) and neuropathic syndromes (of the upper and lower limbs). Conclusions: The data obtained from administering the questionnaire were not sufficient to create a specific path to define the appropriateness of hydrokinesitherapy for some orthopedic-traumatological problems but could be considered a good starting point on which to build future developments through further studies.